The Influence Of International Trade And Exchange Rate On Indonesia's Economic Growth - Kamala, Ayunda Putri; Riyanto, Maya Aulia (Jurnal Ekonomi-Qu, 2024)
International trade is the activity of exchanging goods or services that occurs between one country and another. International trade is very important for economic growth in developed and developing countries, because economic progress is the main factor that determines economic prosperity. International trade and exchange rates have a complex and dynamic relationship with Indonesia's economic growth. Thisresearchaims to determine the influence of international trade and exchange rates on Indonesian economic growth. This research tries to answer the problem regarding the influence of international trade and exchange rates on economic growth. From the results of the research we conducted, it can be said that international trade and exchange rates have a significant influence on Indonesia's economic growth, both partially and simultaneously. International trade has a positive influence, while the exchange rate has a negative influence